The Effect of Life Style and Islamic Branding on Consumer Decisions in Buying Muslim Gamis Fashion Products in Bandar Lampung - Winda Anggraini; Heni Noviarita (BASKARA : Journal of Business and Entrepreneurship, 2021)
Fashion is considered not only as clothing industry but also shows a person's lifestyle in appearance and becomes part of the identity of a group of people. "Gamis" is the trend among Indonesian women especially in Bandar Lampung, in recent years, is an encouraging phenomenon. The fashion industry is supported by various technological advances and the development of sophisticated civilization then it produces several products for its users. This is supported by several sides, both in terms of local designers who are increasingly capable of improving economic levels to the retail sector which is growing significantly. Indonesia has the potential to develop and even become a center for Muslim fashion in the world. This study aims to examine whether Life Style and Islamic Branding can influence purchasing decisions in Muslim fashion. The type of research is field research, and the nature of the research is quantitative descriptive analysis. The sample is consumers who use Muslim clothing products using the Solvin formula totalling 100 people. The data is analyzed using the SPSS version 21 application. The results, variable X1 or Life Style have a significant number below 0.05, which is equal to 0.000, so the hypothesis is accepted. The conclusion is the independent variable, namely Life Style, has a positive effect on the dependent variable, namely Purchase Decision (Y). This is in line with previous research and also the study of the theory of lifestyle on consumer decisions. The results of the research Variable X2 or Islamic Branding has a significant number below 0.05, which is equal to 0.003, so the hypothesis is accepted with the conclusion that the independent variable, namely Islamic branding (X2) has a positive effect on the dependent variable, namely, Purchase Decision (Y). The result is in line with previous research and also with the study of Islamic Branding theory.